RELEVANSI KARUNIA KESEMBUHAN PADA MASA KINI MENURUT KISAH PARA RASUL - Daud Ari Bagus Satria; Ragil Kristiawan; Rudyanto Chandra Saputra (JOURNAL of THEOLOGICAL STUDENTS, 2021)
The gift of healing today is an interesting topic for discussion in Bible research and study. Not a few issues that exist today are pros and cons in his theory. In this scientific paper, the researcher wants to investigate how the word healing power is used in the biblical text, namely in the Book of Acts and see its relevance today. In his research, the researcher uses a biblical approach where qualitative research is descriptive, not numerical. In accordance with the results of the research that the author describes in this scientific paper, the healing power that occurs in the Acts of the Apostles is still relevant today in terms of the tenses used in explaining the gift of healing.